Indonesian Government Protection of Migrant Workers, Social Integration and Discrimination Issues - Muhamad Hasyim; Zainal Arifin Hoesein (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This paper examines the Indonesian government’s policy on migrant worker protection, its relation to social integrity in both origin and destination communities, and the discrimination issues experienced by Indonesian Migrant Workers (PMI). Using a qualitative document and literature review approach, this paper identifies policy gaps, forms of discrimination (interpersonal and institutional), and policy recommendations to strengthen protection and promote social integrity.